Determinants of tuberculosis treatment success at Siti Fatimah Regional Hospital, Palembang - Pulungan, Rafiah Maharani; Liberty, Iche Andriyani; Utami, Anissa Citra; Pratama, Benny Putra; Kirana, Junneka Sarah (Talenta Publisher, 2025)
Tuberculosis (TB) is a chronic infectious disease that remains a public health problem in Indonesia. The success rate of pulmonary TB treatment at Siti Fatimah Regional Hospital, Palembang, in 2024 was 71%, still below the national target of 90%. This study aimed to determine factors associated with the success of pulmonary TB treatment. The analysis showed that age was significantly associated with treatment success, with patients aged <30 years having almost three times the chance of success compared to patients aged ≥30 years (OR=2.87; p=0.000). Residential factors also showed a significant relationship, with patients domiciled in Palembang City having a greater chance of success than patients from outside the city (OR=8.88; p=0.020). Meanwhile, gender and occupation did not show a significant relationship. Further analysis showed that age was the most dominant factor influencing the success of pulmonary TB treatment. These findings emphasize the importance of more intensive therapy supervision in adults and the elderly and the need to strengthen access to healthcare for patients from outside the city.